Analysis Of The Influence Of Consumer Behavior, Product Attributes And Brand Image On Purchasing Decisions Of Pharmaceutical Industry Products Consumers - Frans Sudirjo; Luh Komang Candra Dewi; Elizabeth; Fahrina Mustafa; Sonny Santosa (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this study is to determine whether consumer attitudes, brand perception, and product characteristics all concurrently have a substantial impact on purchasing decisions. This study employs quantitative descriptive techniques along with a survey methodology. The author employs a variety of data collection techniques, including field research and library research, while gathering data for analysis. Open and closed questionnaires were both used by the researcher in this instance. The multiple linear regression analysis model includes the requirement of testing the analysis requirements. A two-way significant test was applied in this investigation. The t-test results demonstrate that the product attribute variables have a significant and favorable influence on the dependent variable (buying decisions), based on the findings of the partial multiple regression test. The dependent variable (buying decision) is significantly and favorably influenced by the brand image variable. The dependent variable (buying decisions) is significantly and favorably influenced by the customer attitude variable. Based on the outcomes of the simultaneous multiple regression test, the F-test results reveal that the three independent variables, namely the product attributes, brand image, and consumer attitude, significantly influence the purchasing decision variable with a significant value of 0.000 and an f-count > f-table value.